Reconstructing Curriculum Epistemology through the Tawhidic Worldview: A Conceptual Framework Based on Syed Muhammad Naquib al-Attas - Meli Fauziah; Aan Hasanah; Tedi Priatna; Qiqi Yuliati Zakiyah (International Journal of Islamic Khazanah, 2026)
This study aims to reconstruct the epistemological foundation of curriculum design through the tawhidic worldview based on the thought of Syed Muhammad Naquib al-Attas. The study is grounded in the argument that the crisis of contemporary education is not merely pedagogical but fundamentally epistemological, reflected in the dominance of secular and fragmented paradigms that separate knowledge from ethical, spiritual, and metaphysical foundations. Using a qualitative approach through a literature review method, this study analyzes primary and secondary sources related to tawhidic worldview, Islamic epistemology, curriculum theory, and contemporary discourses on knowledge integration. The analysis is conducted through conceptual and epistemological reconstruction to identify the foundational structure of knowledge within the tawhidic framework and its implications for curriculum development. The findings reveal that the tawhidic worldview offers an integrated epistemological system grounded in the unity of reality (tawhid), the integration of revelation (naql), reason (‘aql), and spiritual intuition (dhawq), as well as the centrality of adab as the ultimate aim of education. Based on these findings, the study proposes a Tawhidic Curriculum Model consisting of interconnected ontological, epistemological, and axiological dimensions that collectively shape curriculum structure, pedagogy, assessment, and educational outcomes. The model emphasizes vertical, horizontal, and transcendental integration to overcome the dichotomy between religious and modern sciences while fostering holistic human development (insan kamil). This study contributes theoretically by extending al-Attas’s concept of ta’dib into a more systematic and operational framework for curriculum reconstruction and contributes practically by offering a conceptual direction for developing integrative, value-oriented, and transformative Islamic education in contemporary contexts.